Peran Inspektorat Daerah dalam Peningkatan Kualitas Pengelolaan Keuangan Pemerintah Daerah - Siti Adira; Cut Aulita Saputri; Arnita Arnita; Mariana Mariana (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to analyze the role of regional inspectorates in improving the quality of local government financial management, as well as assess the importance of the awareness of the inspectorate institution in carrying out internal supervision functions to prevent corruption. In addition, this study also explores the effectiveness of the implementation of the Government Internal Control System (SPIP) in ensuring efficient, effective, and compliant regional financial management. The methodology used is literature analysis, with searches through the Google search engine using keywords related to education level and knowledge. A systematic literature review (SLR) is conducted to identify, analyze, and evaluate existing data, as well as to provide guidance for future research. The results of the study show that the role of regional inspectorates is very important in improving the quality of regional financial management through effective supervision and in accordance with the provisions of the law. In addition, the awareness of the inspectorate as an internal auditor is very influential in preventing corruption, because internal auditors must have high integrity. The implementation of SPIP has also proven to be effective in monitoring and ensuring that regional financial management is carried out efficiently and in accordance with applicable regulations. This research contributes to understanding the importance of internal supervision in increasing transparency and accountability of local government financial management.